Pengaruh Herding Behaviour, Regret Aversion Bias, Overconfidence, Dan Risk Tolerance Terhadap Keputusan Investasi Pada Generasi Milenial (Studi Kasus Pada PT. Phintraco Sekuritas Pojok Bursa FEB UNIMAL) - Putri, Lidia Syah; Ristati, Ristati Ristati; Husaini, Husaini Husaini; Wardhiah, Wardhiah Wardhiah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This study aims to determine how the influence of herding behavior, regret aversion bias, overconfidence, and risk tolerance on investment decisions in the millennial generation. The data used in this study is primary data obtained by distributing questionnaires to 97 investors who invested in PT. Phintraco Securities Corner of FEB Unimal Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis using the help of SPSS software version 26. The results found that herding behavior and regret aversion bias had an insignificant negative effect on investment decisions. Meanwhile, overconfidence has a negative and significant effect on investment decisions. While risk tolerance has a positive effect on investment decisions at PT. Phintraco Securities Corner of FEB Unimal Stock Exchange. This shows that investors in PT. Phintraco Securities Corner FEB UNIMAL tends to make investment decisions based on fundamental analysis obtained from the company's financial condition and overall economic condition. Then investors also tend to pay attention to facts and data in making investment decisions and not just emotional factors, this is because investors at PT. Phintraco Securities Corner FEB UNIMAL tends to be bolder in taking higher investment risks and can get greater returns in the financial market. Keywords: Investment Decisions, Herding Behaviour, Regret Aversion Bias, Overconfidence, and Risk Tolerance